Pengaruh Kemudahan dan Kepercayaan Terhadap Kepuasan Pengguna Brilink UD. Putra Jaya di Kecamatan Soromandi Kabupaten Bima - Puji Astuti; Intisari Haryanti; Muhajirin Muhajirin (Indo Publishing, 2026)
This study aims to analyze the effect of ease of use and trust on user satisfaction at BRILink UD. Putra Jaya in Soromandi District, Bima Regency. This research employed a quantitative approach with an associative research design. The population consisted of all users of BRILink UD. Putra Jaya, the exact number of which was unknown. Therefore, the sample size was determined using the Lemeshow formula, resulting in 96 respondents selected through purposive sampling. Data were collected through questionnaires, observations, and literature studies. The data were analyzed using SPSS version 27, including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t-tests, and F-tests. The results showed that, partially, ease of use had a positive and significant effect on user satisfaction, with a t-value of 3.271 and a significance value of 0.002 (<0.05). Trust also had a positive and significant effect on user satisfaction, with a t-value of 3.641 and a significance value of 0.000 (<0.05). Simultaneously, ease of use and trust had a significant effect on user satisfaction, with an F-value of 17.124 and a significance value of 0.000 (<0.05). The coefficient of determination (R²) was 0.269, indicating that ease of use and trust explained 26.9% of the variation in user satisfaction, while the remaining 73.1% was influenced by other variables not examined in this study. Based on the findings, it can be concluded that the higher the perceived ease of use and trust, the higher the level of user satisfaction with BRILink UD. Putra Jaya in Soromandi District, Bima Regency.